Misoprostol Inhibits Equine Neutrophil Adhesion, Migration, and Respiratory Burst in an In Vitro Model of Inflammation - Martin, Emily Medlin; Till, Rebecca Louise; Sheats, Mary Katherine; Jones, Samuel L. (Frontiers in Veterinary Science, 2017)
In many equine inflammatory disease states, neutrophil activities such as adhesion, migration and reactive oxygen species (ROS) production become dysregulated. Dysregulated neutrophil activation causes tissue damage in horses with asthma, colitis, laminitis and gastric glandular disease. Nonsteroidal anti-inflammatory drugs (NSAIDS) do not adequately inhibit neutrophil inflammatory functions and can lead to dangerous adverse effects. Therefore, novel therapies that target mechanisms of neutrophil-mediated tissue damage are needed. One potential neutrophil-targeting therapeutic is the PGE1 analog misoprostol. Misoprostol is a gastroprotectant that induces intracellular formation of the secondary messenger molecule cyclic AMP (cAMP), which has been shown to have anti-inflammatory effects on neutrophils. Misoprostol is currently used in horses to treat NSAID-induced gastrointestinal injury, however its effects on equine neutrophils have not been determined. We hypothesized that treatment of equine neutrophils with misoprostol would inhibit equine neutrophil adhesion, migration and ROS production, in vitro. We tested this hypothesis using isolated equine peripheral blood neutrophils collected from 12 healthy adult teaching/research horses of mixed breed and gender. The effect of misoprostol treatment on adhesion, migration and respiratory burst of equine neutrophils was evaluated via fluorescence-based adhesion and chemotaxis assays, and luminol-enhanced chemiluminescence, respectively. Neutrophils were pretreated with varying concentrations of misoprostol, vehicle, or appropriate functional inhibitory controls prior to stimulation with LTB4, CXCL8, PAF, LPS or immune complex (IC). This study revealed that misoprostol pretreatment significantly inhibited LTB4-induced adhesion, LTB4-, CXCL8-, and PAF-induced chemotaxis, and LPS-, IC-, and PMA-induced ROS production in a concentration-dependent manner. This data indicates that misoprostol-targeting of E-prostanoid receptors potently inhibits equine neutrophil effector functions in vitro. Additional studies are indicated to further elucidate the role of EP receptors in regulating neutrophil function. Overall, our results suggest misoprostol may hold promise as a novel anti-inflammatory therapeutic in the horse.